2016
DOI: 10.21276/sjams.2016.4.7.42
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perinatal Asphyxia on Thyroid Stimulating Hormone and Thyroid Hormones

Abstract: Abstract:Less is known about the effect of perinatal asphyxia on fetal and neonatal thyroid hormone levels despite their importance. Only few studies carried out so far on this subject and even these have conflicting results. Aim of our study was to compare the serum levels of thyroid hormone (FT3&FT4) and TSH in term newborns with perinatal asphyxia and in healthy term newborns at 18 to 24 hr. after birth. And to find the association between severity of hypoxic-ischemic Encephalopathy and altered thyroid horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Our findings are similar to the findings of a study conducted by Umesh G. et al and Pereira DN. et al [24,25] however, another study by Borges M. et al found the enrolled neonates, despite a surge in the TSH levels at 5 and 3 hours of birth, T3 and T4 failed to elevate in the asphyxiated group.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings are similar to the findings of a study conducted by Umesh G. et al and Pereira DN. et al [24,25] however, another study by Borges M. et al found the enrolled neonates, despite a surge in the TSH levels at 5 and 3 hours of birth, T3 and T4 failed to elevate in the asphyxiated group.…”
Section: Discussionmentioning
confidence: 93%